2021
DOI: 10.9734/arrb/2021/v36i1130447
|View full text |Cite
|
Sign up to set email alerts
|

Agromorphological Characterization of a Collection of Senna obtusifolia (L.) in Burkina Faso

Abstract: Aims: Senna obtusifolia (L.) is an important wild herbaceous species for subsaharan Africa population. It is used in human food and traditional medicine to treat several deseases. In Burkina Faso, despite its potentialities, this species is of a little interest in scientific research. The aim of this study is to provide a good knowledge of the genetic diversity of this species. Study Design: The experimental design used was a randomized Fischer block type with three replications. Place and Duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…In addition, this group contains the majority of the best agronomic performance accessions from the agromorphological evaluation. According to Nacambo et al [ 11 ], an agromorphological evaluation carried out on these same accessions revealed a group of accessions (group 3) that showed better agronomic performance. The majority of the accessions in genetic group 3 are part of this group that showed better agronomic performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, this group contains the majority of the best agronomic performance accessions from the agromorphological evaluation. According to Nacambo et al [ 11 ], an agromorphological evaluation carried out on these same accessions revealed a group of accessions (group 3) that showed better agronomic performance. The majority of the accessions in genetic group 3 are part of this group that showed better agronomic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Tis research is part of a Ph.D. thesis called "Ethnobotanical Study and Genetic Diversity of a Collection of Senna obtusifolia (L.) Irwin and Barneby in Burkina Faso" [42]. Tis work was carried out during the author's unique PhD thesis at the Université Joseph KI-ZERBO de Ouagadougou.…”
Section: Data Availabilitymentioning
confidence: 99%
See 3 more Smart Citations